Annexin 1: a paracrine/juxtacrine mediator of glucorticoid action in the neuroendocrine system. - Buckingham, J; Solito, E; John, C; Tierney, T; Taylor, A; Flower, R; Christian, H; Morris, J (2003)
Glucocorticoids (GCs) play an essential role in the maintenance of homeostasis. In normal circumstances their secretion is tightly regulated by a complex servo mechanism through which the steroids suppress the synthesis and release of ACTH and its hypothalamic releasing factors (CRH and AVP) and thereby reduce the positive drive to the adrenal cortex. The feedback actions of GCs on hormone release develop rapidly (within minutes), well before any changes in hormone synthesis are apparent. By using immunoneutralization, gene targeting and pharmacological strategies in in vivo and in vitro models, we have identified annexin 1, a Ca(2+)- and phospholipid-binding protein, as a key mediator of the early inhibitory actions of GCs on peptide release. This brief review outlines this work and describes molecular and cellular studies which have provided insight into the mechanism of annexin 1-dependent GC signalling in the neuroendocrine system.